The Ability of Prospective Preservice Elementary School Teachers to Develop Student Worksheets on Context-Based Science Learning - Hamdu, Ghullam; Yulianto, Ade (Mimbar Sekolah Dasar, 2018)
The use of student worksheets (LKS, Lembar Kerja Siswa) can assist teachers in developing and implementing the learning process in the classroom. Prospective elementary school teachers need to be equipped with the ability to develop innovative LKS so that they can be used for learning process. This study aims to identify the ability of prospective elementary school teachers in developing worksheets on context-based science learning through debriefing programs. The stages of the debriefing program consist of: giving initial assignments and understanding, implementing design, and workshops, reviewing/reflecting the design results (group discussions and presentations), and making improvement. This debriefing program was attended by 80 college students from preservice elementary school teacher level four at one university in the West Java region, Indonesia. LKS products before and after debriefing are described based on several aspects and then analyzed to determine the effect of the debriefing program on improving college students' ability in developing LKS. The results show that the debriefing program can lead to the college students' ability to develop LKS on context-based science learning. The improved ability is related to: clarity in the use of written language, concept stages, context use, showing the authenticity of the task and the use of learning media.